The Pharisee's wife [large type] - Oke, Janette, 1935- (Tyndale House, 2025)
"From the beloved author of Love Comes Softly comes an inspiring work of historical fiction about a young Jewish woman, plucked from obscurity and thrust on a perilous journey, only to witness the world's most life-changing story. Like most young women in ancient Israel, Mary has little control over her own destiny. When Enos, a rising Pharisee, sees her one day in the market-the most beautiful woman he has ever laid eyes on-and determines to make her his wife, Mary's fate is quickly sealed. His exorbitant bride price is the only hope her parents have of escaping abject poverty, but surely the fact that such a devout and esteemed man has chosen a girl of her station must be a sign of blessing. When Mary enters training to become the proper Pharisee's wife, it is as though she has been abandoned in a foreign land, where one misstep could cost her greatly. That feeling only deepens when she discovers Enos is all she feared he might be, treating her merely as a prize he has won-and worse. Then rumors of a miracle-working, traveling Prophet change everything, and Mary and Enos are swept up in events that will challenge all they hold dear and forever alter both their futures." -- ONIX annotation.